Coordinate regulation of Cyp2e1 by β-catenin- and hepatocyte nuclear factor 1α-dependent signaling. (28th March 2016) - Groll, Nicola; Petrikat, Tamara; Vetter, Silvia; Colnot, Sabine; Weiss, Frederik; Poetz, Oliver; Joos, Thomas O.; Rothbauer, Ulrich; Schwarz, Michael; Braeuning, Albert
Abstract: Depending on their position within the liver lobule, hepatocytes fulfill different metabolic functions. Cytochrome P450 (CYP) 2E1 is a drug-metabolizing enzyme which is exclusively expressed in hepatocytes surrounding branches of the hepatic central vein. Previous publications have shown that signaling through the Wnt/β-catenin pathway, a major determinant of liver zonation, and the hepatocyte-enriched transcription factor HNF (hepatocyte nuclear factor) 1α participate in the regulation of the gene. This study was aimed to decipher the molecular mechanisms by which the two transcription factors, β-catenin and HNF1α, jointly regulate CYP2E1 at the gene promoter level. Chromatin immunoprecipitation identified a conserved Wnt/β-catenin-responsive site (WRE) in the murine Cyp2e1 promoter adjacent to a known HNF1α response element (HNF1-RE). In vitro analyses demonstrated that both, activated β-catenin and HNF1α, are needed for the full response of the promoter. The WRE was dispensable for β-catenin-mediated effects on the Cyp2e1 promoter, while activity of β-catenin was integrated into the promoter response via the HNF1-RE. Physical interaction of β-catenin and HNF1α was demonstrated by co-immunoprecipitation. In conclusion, present data the first time identify and characterize the interplay of HNF1α and β-catenin and elucidate molecular determinants of CYP2E1 expression in the liver.